Pelanggaran Hak Asasi Manusia pada Kasus Sengketa Lahan Perkebunan Tahun 2012 di Kabupaten Ogan Ilir Provinsi Sumatera Selatan - Saputra, Angga; Taufiq, Muhammad (Universitas Batanghari Jambi, 2024)
Countries all over the world recognize human rights as very important rights and need to be recognized in their constitutions. The protection of human rights is also regarded as an integral part of the rule of law, so States pay primary attention to this concept. Therefore, the security, peace, and stability of a country can be threatened by human rights violations. In this case in Indonesia there are frequent violations of human rights, both serious and mild. One of the allegations of human rights violations was a farmland dispute in Ogan Ilir Province of Sumatra Seiatan which resulted in one victim killed and four people suffered Iuka-Iuka, several human rights were violated, namely: the right to life, the right not to receive cruel treatment, the rights to safety and the rights of the child, and these rights are explicitly guaranteed in Act No. 39 of 1999 on Human Rights.